Systematic review of factors and barriers influencing e‑commerce adoption among SMEs over the last decade: a TOE framework perspective - Ramachandran, Sridar; Kay, Loo Mei; Raja Yusof, Raja Nerina (Springer New York LLC, 2024)
This systematic review critically examines the technological, organizational, and environmental (TOE) factors influencing e-commerce adoption among small and medium-sized enterprises (SMEs) over the past decade. By dissecting the distinct roles of these TOE factors, the review identifies both the facilitators and inhibitors affecting SMEs as they navigate the complexities of e-commerce integration. The analysis reveals that while technological innovations and digital readiness significantly drive adoption, SMEs face persistent challenges related to resource limitations, cybersecurity concerns, and rapid technological change. Organizational readiness, highlighted by change management and strategic alignment, emerges as a critical determinant, whereas the environmental context, including market trends and regulatory policies, shapes the e-commerce landscape within which SMEs operate. This review emphasizes the need for a nuanced understanding of these multidimensional factors and recommends targeted interventions to alleviate barriers. Suggestions for future research include longitudinal studies to track the evolution of e-commerce adoption strategies, the impact of emerging technologies on SMEs’ competitive advantage, and the role of government policy in fostering a supportive ecosystem for digital transformation.